Combined effect of gene-gene interaction on the among the function of thyroid gland and the degree of its enlargement in patients of autoimmune thyroiditis and thyroid adenoma in the inhabitants of Northern Bukovina - M. I. Sheremet (Kazimierz Wielki University, 2017)
Was a comprehensive analysis of combined influence of the gene polymorphisms associated with various links in the regulation of apoptosis (BCL-2, CTLA-4 and APO-1 / Fas) on the development of nodular goiter on the background of autoimmune thyroiditis and thyroid adenoma in the surveyed population with regard to changes in the functional activity of the thyroid gland and the degree of the thyroid gland enlargement has been performed. For this purpose, we used the method of Multifactor Dimensions Reduction 3.0.2 - MDR by calculating the prediction potentials. Established that graphic models of gene-gene interaction with the highest cross-validation consistency created by Multifactor Dimensions Reduction 3.0.2 - MDR method, showed complex "synergistic or independent" impact of polymorphic loci of the CTLA-4 (+ 49G / A), Fas (-1377G / A) and Bcl-2 (63291411A> G) genes on the onset of the change of thyroid function and degree of hyperplasia in the population of residents of Northern Bukovina.